Impacts of tsetse control and land-use on vegetative structure and tree species composition in south-western Ethiopia - Reid, Robin S.; Wilson, C.J.; Kruska, Russell L.; Mulatu, W. (1997)
More effective control of the tsetse fly in Africa will reduce constraints imposed by the livestock disease, trypanosomiasis. Trypanosomiasis lowers livestock productivity, and in some areas, may limit the ability of farmers to keep livestock and plough the land using animal traction. Control of the disease may cause the expansion of livestock populations and cultivated land area which, in turn, may have negative impacts on ecosystem structure and function. The objective of this study was to assess the impacts of tsetse (Glossina morsitans submorsitans, G. pallidipes, G. fuscipes fuscipes) control (using insecticides), through expansion of agricultural land use, on vegetative structure and tree species composition in the Ghibe Valley, SW Ethiopia. This was done by first describing land cover land-use patterns in areas with and without tsetse flies, and then quantifying land-use impacts on vegetation. Land-use/land cover was assessed and quantified by classifying a recent LANDSAT Thematic Mapper (TM) image of the valley and analysing the abundance of cover types in a geographical information system (GIS). Vegetative structure and tree species composition were measured in field plots in 2 types of cultivated fields (oxen and tractor ploughed), and in upland wooded grasslands and riparian woodlands. Land cover in the Ghibe Valley was dominated by wooded grasslands (60) and cultivation (26), with smaller patches of dense upland woodland (9) and sparse woodland strips along river courses (3). Most farms were cultivated by smallholders using oxen (25 of the total cultivated area) with limited areas ploughed by large holders using tractors (0.5). The cover of woody plants was highest in riparian woodlands (53), moderate in oxen-ploughed fields (6) and wooded grasslands (9), and lowest in tractor-ploughed fields (1). Species diversity (Shannon index 'H') was greatest in riparian woodlands (1.6) and smallholder fields (1.4), moderate in grasslands (1.0) and low on largeholder farms (0.7). These results highlight the importance of rare but biologically rich riparian areas, which should be a focus for conservation. If tsetse control, through the expansion of cultivation, causes degradation of these woodlands, the potential for impact is high. However, there appear to be few changes in the vegetation in the process of conversion of wooded grasslands into smallholder fields, which is the likely result of successful tsetse control. A hypothetical model of vegetative change in the Ghibe Valley is described in the light of the vegetative potential of the area and recent changes in the frequency of hunting and burning in the valley.